2023
DOI: 10.3390/molecules28186719
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and Applications of Graphene and Its Derivatives-Based Electrochemical Sensors in Cancer Diagnosis

Li Fu,
Yuhong Zheng,
Xingxing Li
et al.

Abstract: Graphene is an emerging nanomaterial increasingly being used in electrochemical biosensing applications owing to its high surface area, excellent conductivity, ease of functionalization, and superior electrocatalytic properties compared to other carbon-based electrodes and nanomaterials, enabling faster electron transfer kinetics and higher sensitivity. Graphene electrochemical biosensors may have the potential to enable the rapid, sensitive, and low-cost detection of cancer biomarkers. This paper reviews earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 157 publications
(198 reference statements)
0
5
0
Order By: Relevance
“…Nonetheless, electrochemical sensors are similar to optical chemical sensors in terms of sensing element advances and diversity. Recent advances in nanomaterial science have provided various materials for sensing elements, including metal nanoparticles (NPs) and CNMs such as carbon dots, CNTs, and graphene [ 26 , 93 , 94 ]. The integration of fabrication technologies has also enabled the use of nanostructured materials as sensing elements in chemical sensors [ 95 , 96 ].…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
“…Nonetheless, electrochemical sensors are similar to optical chemical sensors in terms of sensing element advances and diversity. Recent advances in nanomaterial science have provided various materials for sensing elements, including metal nanoparticles (NPs) and CNMs such as carbon dots, CNTs, and graphene [ 26 , 93 , 94 ]. The integration of fabrication technologies has also enabled the use of nanostructured materials as sensing elements in chemical sensors [ 95 , 96 ].…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
“… 51 Nanocomposite applications have also been documented for the sensitive electrochemical detection of a broad range of cancer biomarkers, including circulating tumor cells, proteins, DNA mutations, and non-coding RNAs like miRNA, glycoproteins, and metabolites. 52 Recent developments in electrochemical biosensors also utilize polymer nanocomposites (PNCs) containing metallic nanoparticles and carbon nanomaterials to enhance the sensor’s performance, improving diagnostic sensitivity and selectivity. 53 Additionally, electrochemical sensing platforms offer label-free detection, 54 providing a versatile and efficient means to detect cancer-related molecules.…”
Section: Nanocomposites In Cancer Diagnosismentioning
confidence: 99%
“…Graphene is a novel twodimensional carbon material with excellent catalytic, stability and electrical conductivity [26,27]. Because of excellent performance, graphite oxide (GO) has been used as modification material for electrochemical sensors and widely applied in cancer diagnosis, pesticide detection, clinical sample detection and other fields [6,28,29]. It has been shown that MOFs combined with graphene oxide have superior catalytic and conductive properties [30,31].…”
Section: Introductionmentioning
confidence: 99%